ETHNOPSYCHOLOGICAL ASPECTS OF THE PERCEPTION OF THE FEMALE IMAGE IN THE SAYINGS OF VARIOUS PEOPLES - Kilichev Akram Abdusamadovich (Bright Mind Publishing, 2025)
The article reveals the ethnopsychological features of perceiving the female image in Russian and Uzbek proverbs. A multi-level content quantification and archetypal analysis was conducted on a corpus of 1,000 paremias. It has been revealed that both cultures rely on the Mother Guardian archetype, however, in Uzbek material, the sacralization of the female role predominates, while Russian discourse combines reverence with ironic distance. The statistically significant difference in the proportion of negative assessments (7% in Russian versus 9% in Uzbek texts) indicates different cultural reactivity to women's autonomy. The obtained results clarify intercultural gender models and can be applied in translation studies, pedagogy, and state gender policy.
Keywords: Proverb, ethnopsychology, female image, Mother archetype, national mentality, russian proverbs, uzbek proverbs, comparative analysis.